Convergent and divergent styles for problem solving. The perspective of soft systems in experiential learning - Acevedo Borrego, Adolfo (2016)
Systemic complexity of organizations comprising operational, strategic and conceptual levels, they are related functional activities of management and operation. In this context, industrial engineer and processes engineer are developed using various combinations of media and making decisions regarding the allocation of resources and the direction of the organization, which uses systematic tools or "hard" derived from scientific management and tools heuristics or "soft" related to intuition and strategy. The aim of the research is to identify the degree of use of techniques and systematic quantitative or qualitative tools intuitive tools for decision-making. The design of the research is exploratory and descriptive, inferential statistics was used applied to two samples: engineers working in companies and industrial engineering student. The results found two situations in the first engineers in managing stable face-structured environments and complex-amorphous environments alike, either using the tools of scientific management with accurate and quantitative solutions and amorphous tools and heuristic solutions approximate, in the second engineering students show greater predisposition to the use of systematic techniques with little regard for the human aspects. We discuss whether academic teaching industrial engineering techniques are sufficient to solve problems, or conversely, the incorporation of new tools for analysis and decision, less accurate and more approximate and intuitive.